2013
DOI: 10.1016/j.cmet.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Sestrins Activate Nrf2 by Promoting p62-Dependent Autophagic Degradation of Keap1 and Prevent Oxidative Liver Damage

Abstract: Sestrins (Sesns) protect cells from oxidative stress. The mechanism underlying the antioxidant effect of Sesns has remained unknown, however. The Nrf2-Keap1 pathway provides cellular defense against oxidative stress by controlling the expression of antioxidant enzymes. We now show that Sesn1 and Sesn2 interact with the Nrf2 suppressor Keap1, the autophagy substrate p62, and the ubiquitin ligase Rbx1 and that the antioxidant function of Sesns is mediated through activation of Nrf2 in a manner reliant on p62-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
402
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(432 citation statements)
references
References 34 publications
13
402
4
Order By: Relevance
“…One is by upregulating NFE2L2 (nuclear factor, erythroid derived 2, like 2) signaling and thereby promoting the expression of genes for antioxidant enzymes. 29 The other is by blocking MTOR activation, which results in ROS accumulation. 23,24,46 The SESN2-promoted mitophagy in our study provides the third pathway for SESN2 to suppress ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One is by upregulating NFE2L2 (nuclear factor, erythroid derived 2, like 2) signaling and thereby promoting the expression of genes for antioxidant enzymes. 29 The other is by blocking MTOR activation, which results in ROS accumulation. 23,24,46 The SESN2-promoted mitophagy in our study provides the third pathway for SESN2 to suppress ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Under oxidative stress, SESN2 serves as an adapter protein that mediates the interaction between SQSTM1 and KEAP1, which results in the autophagic degradation of KEAP1. 29 In a recent study, SESN2 was shown to also induce autophagic degradation of SQSTM1 by promoting ULK1-mediated SQSTM1 phosphorylation via its interaction with ULK1 and SQSTM1. 38 Based on these data and our result that SESN2 induces mitophagy by mediating SQSTM1 binding to ubiquitinated mitochondria via its interaction with SQSTM1, we speculate that SESN2 may be involved in SQSTM1-mediated autophagic degradation through its binding to SQSTM1 and/or SQSTM1 target proteins in response to various cellular stresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sestrin (Sesn2) induction invokes p62, a competitive antagonist of Keap1, which mimics the binding of the ETGE motif of Nrf2 to the kelch domain, but only under overexpressed conditions of Sesn2. Under normal conditions, p62 does not replace Nrf2 binding antagonistically because of the weak binding it projects on Keap1 as compared to the ETGE motif (Bae et al 2013). …”
Section: Peptide Inhibitorsmentioning
confidence: 99%